Family as a Lost Chronotope: Themes of Disintegration and Memory in Contemporary Prose from the Magazine "Daktil" - Altayevna, Sabirova Dina (Journal of Cultural Analysis and Social Change, 2026)
This article analyzes the depiction of family as a lost chronotope in contemporary Kazakhstani prose, primarily represented by the literary magazine "Daktil." The aim of the study is to identify the key themes of disintegration, memory, and loneliness that shape the specific model of the family world in the 21st century. Particular attention is paid to comparing the classical notion of family in the Kazakh literary tradition with the contemporary understanding of kinship ties, which are undergoing significant changes under the influence of social and cultural transformations. The paper examines the evolution of the family image: from the sacred system of clan relations and moral norms in 19th-20th-century literature to the fragmented, vulnerable, and psychologically charged structure of contemporary prose. An analysis of the works of Nastya Kukushkina, Lena Kuznetsova, and Zhanat Zhumataeva reveals how family memory, loss, and disunity become dominant artistic motifs. It is shown that the short fiction of the magazine "Daktil" captures family relationships as a space of conflict, internal isolation, and disrupted communication, where loneliness arises within the family rather than outside it. Particular attention is paid to the interpretation of women's writing, which offers new ways of articulating traumatic experiences associated with motherhood, divorce, the breakdown of family ties, and the search for emotional support. The analysis demonstrates that contemporary Kazakh literature addresses the theme of family not only as a social institution but also as a symbol of cultural memory. In the context of post-Soviet transformation, family is becoming a crucial space for identity formation, where individual experience, collective memory, and societal expectations intersect. The results suggest the emergence of a new family paradigm in 21st-century Kazakh prose.